Computational investigation of the radical‐mediated mechanism of formation of difluoro methyl oxindoles: Elucidation of the reaction selectivity and yields - Thanachon Somnarin; Pacharaporn Krawmanee; M. Paul Gleeson; Duangkamol Gleeson (Journal of Computational Chemistry, 2022)
Abstract Oxindoles are an important class of heterocyclic alkaloids with demonstrated pharmacological activity at multiple biological targets. Preparation of new analogs through novel synthetic routes is therefore highly attractive. In this work, we report a computational study to investigate the synthesis of ethoxycarbonyldifluoromethylated oxindoles from N ‐arylmethacrylamides. The reaction tolerates a diverse range of acrylamides, shows yields ranging from approximately 38%–96%. We have applied density functional theory (DFT) to explore the reaction mechanism, kinetics and thermodynamics to gain further understanding. We demonstrate that a radical‐based ring closure reaction is energetically more favorable than a heterolytic process, that the rate‐determining step is the formation of the arylmethacrylamide radical, and that the product yields and selectivities are consistent with experiment. The results demonstrate that theoretical methods can prove useful to understand how such reaction and could be potentially employed to rapidly explore the reaction scope further.
Keywords: Fluorine in Organic Chemistry; Radical Photochemical Reactions; Oxidative Organic Chemistry Reactions